2021
DOI: 10.3390/su14010003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Public Policy Decision-Making in Smart Cities: Does Extant Theory Support Achievement of City Sustainability Objectives?

Abstract: Evidence-based decision making is promoted as offering efficiency and effectiveness; however, its uptake has faced barriers such as underdeveloped supporting culture, limited access to evidence, and evidence that is not fully relevant. Smart city conceptualizations offer economic and environmental sustainability and better quality of life through evidence-based policy decision-making. We wondered whether smart city theory and practice has advanced the knowledge of evidence-based decision-making. We searched ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Questions can be asked, for example, whether general assumptions about the solution uh it's a longof "smart cities" are based on evidencebased conclusions, or whether they are more or less unfounded guesses. A potential security incident could put such overly optimistic expectations into another perspective [2]. It is necessary to directly assume that any processes and models, including the modernization of cities, will bring with them positive and negative impacts, including the building of new barriers (digital divide, etc.)…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Questions can be asked, for example, whether general assumptions about the solution uh it's a longof "smart cities" are based on evidencebased conclusions, or whether they are more or less unfounded guesses. A potential security incident could put such overly optimistic expectations into another perspective [2]. It is necessary to directly assume that any processes and models, including the modernization of cities, will bring with them positive and negative impacts, including the building of new barriers (digital divide, etc.)…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Only a few authors undertook research on a global scale and compared cities worldwide [22,23]. Others provided more general literature reviews or analyses that did not specify location [8,24]. The majority of the research was undertaken in European cities (32) as shown in Table 1.…”
Section: Location Of Studiesmentioning
confidence: 99%
“…Effective SC management should enhance technology infrastructure, engage stakeholders, adhere to strategic, tactical, and operational levels via efficient criticism and feedback, and implement a bottom-up strategy [6,24]. An open citizen service operating system that utilizes automatic classification boosts citizens' participation.…”
Section: Smart Urban Governancementioning
confidence: 99%
See 1 more Smart Citation
“…Smart cities are defined as smartness both in how their governments harness technologies as well as in how they monitor, analyze, plan, and govern the city [62]. Hence, smart cities can easily be conceptualized based on the Smart City Wheel, developed by Dr. Boyd Cohen [63,64] in which a smart city is defined as the integration of the following six attributes: Smart People; Smart Government; Smart Environment; Smart Economy; Smart Mobility and Smart Living.…”
Section: Smart Cities Conceptual Frameworkmentioning
confidence: 99%